Children and Employment – Resource or Stressors after Breast Cancer? - Ebenhan, K.; Leuteritz, K.; Barthel, Y.; Beutel, M. E.; Papsdorf, K.; Weissflog, G.; Brähler, E. (Geburtshilfe und Frauenheilkunde, 2013)
Introduction: Breast cancer patients suffer clinically relevant levels of psychological stress because of their disease. Various factors can affect the level of stress experienced. This study aimed to investigate the relationship between the level of psychological stress and employment and children, including time since diagnosis. Material and Methods: A randomised clinical study was done of 724 breast cancer patients aged between 18 and 65 years; all were in the curative stage of disease and had been diagnosed 0–12 months previously. Patients were investigated for their levels of psychological stress (anxiety and depression) using the Hospital Anxiety and Depression Scale (HADS). The relationship between anxiety and depression and the variables “employment”, “parenthood” and “time since diagnosis” were investigated, using univariate and multivariate analysis. Results: Patients with a longer time since diagnosis (4–12 months) were found to have lower levels of anxiety (6.28) compared to patients who had been diagnosed only 0–3 months previously (7.24; p < 0.01). There was no unambiguous relation between parenthood and anxiety. The age of the children was crucial. Even when results were controlled for patient age, the anxiety levels of women with children below the age of 16 years were significantly higher (7.84) compared to patients without children (6.42) or patients whose children were older than 16 years (6.87; p = 0.04). Women who were not employed had significantly higher levels of depression compared to all other participants in the study (p = 0.02). No reciprocal effects were found between investigated variables. Conclusion: We found a differentiated relationship between the variables “time since diagnosis”, “employment” and “children” and the level of psychological stress experienced by breast cancer patients. When determining the level of psychological stress in the 1st year after diagnosis, particular attention should be paid to patients who are not employed and patients with children below the age of 16 years.
Keywords: breast cancer; psychological stress; children; time since diagnosis; employment status